Analisis Perbandingan Kinerja Saham Perusahaan Manufaktur Terindeks Syariah dan Konvensional - Arisa Dwi Amalia; Dwi Kartikasari (Politeknik Negeri Batam, 2016)
This study tried to analyze the company's stock performance comparison of manufacturing company with Islamic index and conventional index listed in Jakarta Islamic Index (JII) and Indonesia Stock Exchange (BEI) during 2011 -2015. Companies are grouped into manufacturing companies with Islamic index and conventional index. The analysis was performed by calculating the stock returns and Sharpe index then compares the results using independent sample t-test in SPSS version 20. The calculation of returns showed that conventional manufacturing company has a better performance based on the average return every year. But according to Sharpe index value, manufacturing company with Islamic index has a smaller risk and arguably better ensure security even with smaller return. T-test result stated there was no significant difference to the stock performance of manufacturing companies with Islamic index and conventional index.